Engagement, Retention, and Progression to Type 2 Diabetes: A Retrospective Analysis of the Cluster-Randomised "Let's Prevent Diabetes" Trial. - Laura J Gray; Thomas Yates; Jacqui Troughton; Kamlesh Khunti; Melanie J Davies; Let’s Prevent Diabetes Team (PLoS Medicine)
Background Prevention of type 2 diabetes mellitus (T2DM) is a global priority. Let's Prevent Diabetes is a group-based diabetes prevention programme; it was evaluated in a cluster-randomised trial, in which the primary analysis showed a reduction in T2DM (hazard ratio [HR] 0.74, 95% CI 0.48-1.14, p = 0.18). We examined the association of engagement and retention with the Let's Prevent Diabetes prevention programme and T2DM incidence. Methods and findings We used data from a completed cluster-randomised controlled trial including 43 general practices randomised to receive either standard care or a 6-h group structured education programme with an annual refresher course for 2 y. The primary outcome was progression to T2DM at 3 y. The characteristics of those who attended the initial education session (engagers) versus nonengagers and those who attended all sessions (retainers) versus nonretainers were compared. Risk reduction of progression to T2DM by level of attendance was compared to standard care. Eight hundred and eighty participants were recruited, with 447 to the intervention arm, of which 346 (77.4%) were engagers and 130 (29.1%) were retainers. Retainers and engagers were more likely to be older, leaner, and nonsmokers than nonretainers/nonengagers. Engagers were also more likely to be male and be from less socioeconomically deprived areas than nonengagers. Participants who attended the initial session and at least one refresher session were less likely to develop T2DM compared to those in the control arm (30 people of 248 versus 67 people of 433, HR 0.38 [95% CI 0.24-0.62]). Participants who were retained in the programme were also less likely to develop T2DM compared to those in the control arm (7 people of 130 versus 67 people of 433, HR 0.12 [95% CI 0.05-0.28]). Being retained in the programme was also associated with improvements in glucose, glycated haemoglobin (HbA1c), weight, waist circumference, anxiety, quality of life, and daily step count. Given that the data used are from a clinical trial, those taking part might reflect a more motivated sample than the population, which should be taken into account when interpreting the results. Conclusions This study suggests that being retained/engaged in a relatively low-resource, pragmatic diabetes prevention programme for those at high risk is associated with reductions in the progression to T2DM in comparison to those who receive standard care. Nonengagers and nonretainers share similar high-risk traits. Service providers of programmes should focus on reaching these hard-to-reach groups. Trial registration ClinicalTrials.gov ISRCTN80605705.